Komunikasi: Nyata, Maya dan Hubungannya dengan Pendidikan - Primadi Tabrani (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2012)
Human communication is the topic of this article. It begins with Direct-Contact Communication in prehistory and during childhood. Than follows Distance-Communication that begins with talking, than writing and reading follows. Since the beginning there are always criticism every time a new communication media emerge. This criticism accelerate with the habit of indulging reading literature in the train, chatting by amateur radio and end up in BB's cyberspace and its facebook. Besides its positive effect, we are intoxicated by this IT communication. So we loose many productive hours of working time. The IT (Information Technology) becomes frightening with its